Combinatorial effect of different alginate compositions, polycations, and gelling ions on microcapsule properties - Loh, Qiu Li (2013)
Microencapsulation technology is commonly used to deliver cells and drugs for therapeutic applications. The encapsulation material has a direct influence over the properties of microcapsules and will eventually dictate the efficacy of this delivery system. In this study, the combinatory effect of different alginate compositions, polycations and gelling ions was investigated to determine their roles in affecting the properties of the microcapsules. A multifactorial relationship was found between the three factors, in which certain factors took priority over others in influencing the overall property of the microcapsules. As the size of the microcapsules was kept constant throughout the investigation, further insights into the role of fabrication parameters on microcapsules size were also obtained. From the results, poly-L-lysine-coated microcapsules fabricated from 40/60 sodium alginate and cross-linked with barium chloride were the most ideal for applications that require both good mechanical as well as diffusion properties.